2020
DOI: 10.1055/a-1161-8984
|View full text |Cite
|
Sign up to set email alerts
|

Is Prematurity a Protective Factor Against Developmental Dysplasia of the Hip? A Retrospective Analysis of 660 Newborns

Abstract: Purpose In Middle Europe developmental dysplasia of the hip (DDH) has an incidence of up to 5.9 %. The rate of congenital hip dislocation as the worst complication of a growth disorder of the hip is between 1.5 % and 2.5 %. Among known risk factors of DDH are breech position, multiples, foot deformities and family history. The aim of this retrospective study was to investigate prematurity as a risk factor for developmental dysplasia of the hip (DDH). Materials and Methods The hips of 283 infants who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 8 publications
2
8
0
2
Order By: Relevance
“…Smaller infants have more space in the pelvis and thus Ortolani positivity is not common. Our result is in agreement with some recent previous studies [24,25]. There are also controversial results.…”
Section: Discussionsupporting
confidence: 92%
“…Smaller infants have more space in the pelvis and thus Ortolani positivity is not common. Our result is in agreement with some recent previous studies [24,25]. There are also controversial results.…”
Section: Discussionsupporting
confidence: 92%
“…Smaller infants have more space in the pelvis and thus Ortolani positivity is not common. Our result is in agreement with some recent previous studies [22,23]. There are also controversial results.…”
Section: Discussionsupporting
confidence: 92%
“…Duramaz et al [29] demonstrated an increase in acetabular maturity with increased gestational age using the Graf classification system. Koob et al, [26] Lange et al, [27] and Orak et al [23] all hypothesized that the increased maturity in fetal hips in preterm infants is related to decreased intrauterine restrictions. This would allow for muscular, cartilaginous and bone development to theoretically occur unhindered.…”
Section: Discussionmentioning
confidence: 99%